Special ultralow-temperature anti-wear lubricating grease for robot

By embedding stress-responsive microencapsulated repair agents into grease, a self-healing lubricating film is constructed, solving the problem of increased viscosity and embrittlement of traditional grease at ultra-low temperatures. This achieves efficient wear resistance and fault warning for robot joints, making it suitable for robot joint lubrication in extreme environments.

CN121991740APending Publication Date: 2026-05-08SHENGBAO ROAD PETROCHEMICAL (TIANJIN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610058625.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-16
Publication Date
2026-05-08

AI Technical Summary

Technical Problem

Traditional greases exhibit a dramatic increase in viscosity and embrittlement of the lubricating film at ultra-low temperatures, leading to irreversible wear. Furthermore, they lack effective self-repair mechanisms, making it impossible to guarantee reliability and detect early signs of failure in robot joints.

Method used

Employing a biomimetic self-healing mechanism, a stress-responsive lubricating film is formed by embedding microencapsulated repair agents into the base oil-thickener composite system. This film can trigger an endogenous chemical repair reaction when micro-damage occurs, rebuild the protective interface, and enhance lubrication performance and fault detection capabilities.

Benefits of technology

It significantly improves the operational reliability, resistance to fretting wear, and fault precursor detection capabilities of robot joints in a wide temperature range of -70℃ to 25℃, reduces system complexity, and extends the service life of the joints.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of lubricating materials, and discloses ultralow-temperature anti-wear lubricating grease special for a robot. The lubricating grease is composed of 85%-92% of base oil, 6%-10% of a composite thickening agent, 1%-3% of a microencapsulation repairing agent and 0.5%-2% of an auxiliary additive. Wherein the microcapsule has a stress response type fracture characteristic, dicyclopentadiene and triethyl aluminum are released during local damage, and a high-hardness repair film is generated through in-situ polymerization; the composite thickening agent ensures thixotropic stability in a wide temperature range, and a base oil blending system ensures low viscosity and elasticity at-70 DEG C. According to the invention, a basic oil-composite thickening agent-stress response microcapsule three-in-one bionic lubricating system is constructed, so that the problem of irreversible wear caused by film embrittlement of traditional lubricating grease at-70 DEG C is solved; invalid consumption of the repairing agent is avoided; and the structural stability of the repairing film in subsequent operation is ensured. The method is suitable for application scenes such as polar region scientific investigation robots, deep space exploration mechanical arms and ultralow-temperature cold chain transfer robots which have strict requirements on joint reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lubrication materials technology and relates to a special low-temperature anti-wear grease for robots. Background Technology

[0002] As the most commonly used interfacial medium in spherical bearings and transmission mechanisms, grease not only needs to provide basic friction reduction and anti-wear functions, but also needs to maintain the structural integrity and dynamic repair capability of the lubricating film under severe temperature changes and high-frequency fretting loads. Although traditional mineral oil or synthetic hydrocarbon-based greases perform well at room temperature and general low temperature conditions, their molecular chain segments tend to become rigid due to significant attenuation of thermal motion in ultra-low temperature environments. This leads to a sharp increase in the viscosity of the base oil and embrittlement of the soap-based thickener network, which macroscopically manifests as a loss of lubricating film extensibility and a sharp drop in shear strength.

[0003] Existing grease systems mostly rely on physical adsorption or boundary film formation mechanisms to form a protective layer. Once this film is microscopically broken due to instantaneous impact loads or uneven frictional heat during cold starts, it cannot be regenerated in situ due to the lack of effective material transport and chemical response mechanisms.

[0004] During continuous robot operation, localized dry friction areas can rapidly expand, leading to micro-spot welding and furrowing effects on the contact surfaces. This can cause fluctuations in joint torque, drift in positioning accuracy, and even sudden jamming. The failure modes of more traditional greases are highly insidious—initial wear often shows no obvious signs, and by the time the fault appears, critical components have already suffered irreversible damage, which is particularly dangerous in unattended or remote operation scenarios.

[0005] In recent years, although nanoparticles or extreme pressure additives have been added to enhance film strength, these methods are prone to causing dispersion stability degradation or catalytic side reactions at ultra-low temperatures, which in turn exacerbates the complexity and uncertainty of lubrication systems. In nature, biological tissues (such as skin and blood vessels) can achieve autonomous recovery of structure and function through cascade biochemical reactions triggered by endogenous repair factors after damage. This mechanism provides a new direction for the intelligent evolution of lubrication materials. Summary of the Invention

[0006] To achieve the above-mentioned objectives, this invention provides a robot-specific ultra-low temperature anti-wear grease. The grease is constructed based on a biomimetic self-healing mechanism. By embedding a microencapsulated repair agent with stress-responsive cracking characteristics into a base oil-thickener composite system, the lubricating film can trigger an endogenous chemical repair reaction when it suffers micro-damage under ultra-low temperature conditions, and rebuild a protective interface with complete load-bearing capacity in situ. This significantly improves the operational reliability, anti-fretting wear performance, and fault precursor detection capability of robot joints in a wide temperature range of -70℃ to 25℃.

[0007] The lubricating grease of this invention is composed of the following components by mass percentage: 85%-92% base oil, 6%-10% composite thickener, 1%-3% microencapsulated repair agent, and 0.5%-2% auxiliary additives. The components work synergistically to form a multi-level lubrication structure with dynamic damage response and self-repair capabilities.

[0008] The base oil is a blend of perfluoropolyether and hydrogenated styrene-isoprene block copolymer in a mass ratio of (70:30) to (85:15). The perfluoropolyether has a number-average molecular weight of 2500, a pour point below -80°C, and a kinematic viscosity of 80 mmHg at 40°C. 2 The styrene-isoprene block copolymer exhibits excellent low-temperature fluidity and chemical inertness. With a styrene content of 28% and a Tg of -65℃, it retains rubbery elasticity even at -70℃, effectively suppressing viscosity abrupt changes in the base oil at extreme low temperatures and providing a flexible dispersion medium for microcapsules. After blending, the apparent viscosity at -70℃ is controlled below 12000 mPa·s, meeting the low starting torque requirements of robot joints.

[0009] The composite thickener is composed of lithium 12-hydroxystearate and fluorinated modified montmorillonite in a mass ratio of (4:1) to (6:1). Lithium 12-hydroxystearate acts as the main thickener, forming a three-dimensional fibrous network structure in the base oil. The fiber diameter is 20-50 nm, the length is 200-500 nm, and the network pore size is concentrated in the range of 80-150 nm. The fluorinated modified montmorillonite, after being intercalated with hexadecyltrimethylammonium bromide, has an increased interlayer spacing of 3.2 nm and is further modified with a surface fluorosilane coupling agent to ensure good compatibility with the perfluoropolyether matrix. This composite thickener maintains stable thixotropic properties at -70°C, with a yield stress of 18-25 Pa and a storage modulus G′ greater than the loss modulus G″, ensuring that the grease does not separate during static storage and softens rapidly under dynamic shear to reduce frictional resistance.

[0010] The microencapsulated repair agent is a core-shell structured microsphere with an average particle size of 5-15 μm and a standard deviation of particle size distribution of less than 2 μm. Its core is a 1:1 molar mixture of dicyclopentadiene and triethylaluminum, and the shell is a hybrid cross-linked network of urea-formaldehyde resin and nano-silica. The shell thickness is 0.3-0.6 μm, the Young's modulus is 2.5-3.8 GPa, and the fracture strain is 8%-12%. This mechanical parameter design allows the microcapsules to remain intact under the shear stress (typically less than 0.5 MPa) experienced during normal operation of the lubricating membrane, while undergoing controlled rupture when the local pressure exceeds 1.2 MPa due to contact stress concentration in areas of local micro-damage, releasing the repair agent. Dicyclopentadiene, as a ring-opening metathesis polymerization monomer, and triethylaluminum, as a Grubbs-type catalyst precursor, undergo catalytic polymerization immediately upon contact with the metal surface, generating a highly cross-linked polydicyclopentadiene film with a thickness of 200-500 nm within 30 seconds, a hardness of 0.8-1.2 GPa, and a friction coefficient of less than 0.08, effectively filling microcracks and restoring the interfacial load-bearing capacity.

[0011] The auxiliary additives include antioxidants, metal passivators, and rheology modifiers. The antioxidant is 2,6-di-tert-butyl-p-cresol, added at 0.3%; the metal passivator is N,N′-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine, added at 0.1%; and the rheology modifier is fumed silica with a specific surface area of ​​200 m². 2 / g, with an addition amount of 0.6%. The above additives work together to inhibit the oxidative degradation of base oil during long-term thermal cycling and prevent premature reaction of catalytic remediation agents such as copper and iron ions.

[0012] In a preferred embodiment of the present invention, the shell of the microencapsulated repair agent is doped with magnetic nanoparticles, the composition of which is Fe3O4, the particle size is 8-12 nm, and the doping concentration is 0.5% of the shell mass. This design allows the microcapsules to be directionally enriched in lubricating grease through an external magnetic field, which is particularly suitable for localized enhanced lubrication of specific high-wear areas in robot joints (such as the meshing area of ​​the flexible gear in a harmonic reducer). During the assembly stage, by applying a 0.1T pulsed magnetic field for 5 seconds to the outer ring of the joint bearing, the concentration of microcapsules in the target area can be increased to 2.3 times the overall average, thereby improving the damage response sensitivity of critical parts.

[0013] In another preferred embodiment of the present invention, the microencapsulated repair agent adopts a double-shell structure, with an inner shell of polyurea and an outer shell of fluorinated polyacrylate. The inner shell has a thickness of 0.2 μm and is responsible for encapsulating the repair agent and providing initial mechanical strength; the outer shell has a thickness of 0.15 μm, a surface energy of 18 mN / m, and an interfacial tension with the perfluoropolyether matrix of less than 2 mN / m, which significantly improves the dispersion stability of the microcapsules at ultra-low temperatures.

[0014] The preparation method of the lubricating grease of the present invention includes the following steps: First, under nitrogen protection, perfluoropolyether and hydrogenated styrene-isoprene block copolymer are mixed and stirred at 60°C for 2 hours to form a homogeneous base oil; Second, lithium 12-hydroxystearate and fluorinated modified montmorillonite are added to the base oil, and high-speed shear emulsification is carried out at 85°C for 30 minutes, followed by saponification reaction at 120°C for 1 hour, and then rapidly cooled to -20°C to form a thickened network; Third, microencapsulated repair agent and auxiliary additives are stirred at low speed at 25°C for 15 minutes to avoid shear damage to the microcapsule structure; Finally, the above two parts are vacuum mixed at 40°C for 30 minutes to remove air bubbles, thus obtaining the finished lubricating grease.

[0015] The application of the lubricating grease in robot joints is as follows: When the joint is started and running in an environment of -70℃, the lubricating film covers the contact interface between the rolling elements and the raceways; if the local film thickness is lower than the critical value (<50nm) due to instantaneous overload or uneven cold start, micron-level cracks are generated in the contact area, and local stress concentration causes the adjacent microcapsule shells to rupture, releasing dicyclopentadiene and triethylaluminum; after contact with the metal surface, the two immediately undergo ring-opening metathesis polymerization to generate a continuous and dense polydicyclopentadiene repair film; this film is chemically bonded to the base metal through Al-O-Fe, with a bonding strength greater than 40MPa.

[0016] Compared with the prior art, the beneficial effects of the present invention are: The grease of this invention features damage accumulation monitoring. Because microcapsule rupture is accompanied by a change in local dielectric constant, the integrity of the lubricating film can be monitored in real time using a miniature capacitive sensor integrated into the joint bearing housing. When the number of microcapsules ruptured per unit time exceeds a threshold, the system determines it as an early wear warning and triggers a maintenance command. This function eliminates the need for additional vibration or temperature sensors, reducing the complexity of the robot's health management system.

[0017] This invention, through the construction of a biomimetic lubrication system integrating base oil, composite thickener, and stress-responsive microcapsules, achieves for the first time the active interface repair function of lubricating grease in ultra-low temperature environments. Its technical effects are manifested in the following aspects: First, it solves the problem of irreversible wear caused by film embrittlement in traditional lubricating greases at -70℃; second, through the on-demand release mechanism of the microcapsules, it avoids the ineffective consumption of the repair agent in a non-damaged state; third, the repair product forms a strong chemical bond with the metal substrate, ensuring the structural stability of the repair film during subsequent operation; fourth, the physical properties of the microcapsules endow the lubricating grease with built-in damage sensing capabilities, providing a data foundation for predictive maintenance. This invention is applicable to applications with stringent joint reliability requirements, such as polar scientific research robots, deep space exploration robotic arms, and ultra-low temperature cold chain handling robots, filling a gap in the field of intelligent lubrication materials. Detailed Implementation

[0018] This invention provides a robot-specific ultra-low temperature anti-wear grease. Its technical solution is based on a biomimetic self-healing mechanism. By embedding a microencapsulated repair agent with stress-responsive cracking characteristics into a base oil-thickener composite system, the lubricating film can trigger an endogenous chemical repair reaction when it suffers micro-damage under ultra-low temperature conditions. This allows for the in-situ reconstruction of a protective interface with complete load-bearing capacity, thereby significantly improving the operational reliability, anti-fretting wear performance, and fault precursor detection capability of robot joints in a wide temperature range of -70℃ to 25℃.

[0019] The technical solution of the present invention will be described in detail below with reference to specific embodiments and comparative examples, so as to ensure that those skilled in the art can fully understand and implement the present invention.

[0020] Example 1: Base oil (perfluoropolyether: hydrogenated styrene-isoprene block copolymer = 78:22); composite thickener (lithium 12-hydroxystearate: fluorinated modified montmorillonite = 5:1); microencapsulated repair agent 2% (single-shell structure, particle size 10μm); auxiliary additives 1.0%; Preparation process: Base oil blending → Saponification of composite thickener → Rapid cooling and thickening → Microcapsule + additive mixing → Vacuum degassing → Finished product.

[0021] Example 2: The microcapsules consist of a polyurea inner shell and a fluorinated polyacrylate outer shell, with the remaining formulation and process being the same as in Example 1; Preparation process: Same as in Example 1 (microcapsule structure adjustment).

[0022] Example 3: Base oil ratio 70:30, other formulations and processes are the same as in Example 1; Preparation process: Same as in Example 1 (base oil ratio adjusted).

[0023] Example 4: Base oil ratio 85:15, other formulations and processes are the same as in Example 1; Preparation process: Same as in Example 1 (base oil ratio adjusted).

[0024] Example 5: 1% microencapsulated repair agent, the rest of the formula and process are the same as in Example 1; Preparation process: Same as in Example 1 (adjustment of microcapsule addition amount).

[0025] Example 6: 3% microencapsulated repair agent, the rest of the formula and process are the same as in Example 1; Preparation process: Same as in Example 1 (adjustment of microcapsule addition amount).

[0026] Example 7: The microcapsule shell is doped with 0.5% Fe3O4 nanoparticles, and the rest of the formulation and process are the same as in Example 1; Preparation process: Same as in Example 1 (magnetic particles are added during microcapsule preparation).

[0027] Example 8: The ratio of composite thickener is 4:1, and the rest of the formulation and process are the same as in Example 1; Preparation process: Same as in Example 1 (thickener ratio adjusted).

[0028] Comparative Example 1: No microcapsule repair agent; the rest of the formulation and process are the same as in Example 1. Preparation process: Base oil blending → Saponification of composite thickener → Rapid cooling and thickening → Additive mixing → Vacuum degassing → Finished product.

[0029] Comparative Example 2: The base oil was a single perfluoropolyether; the thickener was pure lithium 12-hydroxystearate; there were no microcapsules; the rest of the process was the same as in Example 1; Preparation process: Base oil → Thickener saponification → Rapid cooling → Additive mixing → Finished product.

[0030] Test method: Ultra-low temperature performance testing: apparent viscosity at -70℃ was measured using a rotational rheometer; a low-temperature bath was used to simulate a wide temperature range from -70℃ to 25℃, and torque fluctuations were monitored.

[0031] Wear resistance and repair testing: The wear scar diameter and PB value were tested using a four-ball machine; the microcapsule rupture pressure was tested using a stress loading device; and the repair film thickness was observed using a scanning electron microscope.

[0032] Stability testing: Determine the microcapsule aggregation rate during storage; test the dropping point and long-term operational reliability; evaluate chemical stability.

[0033] The test data comparisons are shown in Table 1 and Table 2.

[0034] Table 1 Comparison of Apparent Viscosity, Four-Ball Wear Scar Diameter, and PB Value at -70℃ Test Project Apparent viscosity at -70℃ (mPa・s) Four-ball wear scar diameter (mm) PB value (N) Example 1 10500 0.32 850 Example 2 10200 0.3 860 Example 3 11800 0.35 830 Example 4 9800 0.31 870 Example 5 10800 0.36 820 Example 6 10000 0.29 880 Example 7 10300 0.3 850 Example 8 11200 0.34 840 Comparative Example 1 12500 0.68 720 Comparative Example 2 15000 0.75 680 Table 2 Comparison of Repair Membrane Thickness, Torque Fluctuation, and Microcapsule Aggregation Rate Test Project Repair film thickness (nm) Torque fluctuation (±%) Microcapsule aggregation rate (%) Example 1 350 2.8 4.2 Example 2 380 2.4 2.5 Example 3 320 3 4.5 Example 4 360 2.5 4 Example 5 280 3.2 3.8 Example 6 420 2.3 5 Example 7 370 2.6 4.3 Example 8 330 2.9 4.1 Comparative Example 1 - sudden rise - Comparative Example 2 - Stuck - Examples 1-8 showed ultra-low temperature viscosity ≤11800mPa・s and wear scar diameter ≤0.36mm, which were far superior to the comparative examples. Comparative example 1 suffered severe film embrittlement and wear due to the lack of self-healing microcapsules, while the traditional system in comparative example 2 had poor ultra-low temperature performance. This demonstrates that blended base oil + composite thickener + stress-responsive microcapsules are the key to ultra-low temperature anti-wear.

[0035] Double-shell microcapsules (Example 2) improve dispersion stability and repair efficiency; the proportion of perfluoropolyether in the base oil increases (Example 3→1→4), and the viscosity at ultra-low temperature decreases; the amount of microcapsules added increases (Example 5→1→6), and the anti-wear properties and repair effects are optimized simultaneously.

[0036] The embodiment is adapted to ultra-low temperature conditions of -70℃, meeting the needs of extreme environments such as polar regions and deep space; the self-healing function avoids irreversible wear and extends the life of robot joints; the torque fluctuation is small, ensuring operational accuracy; the manufacturing process is compatible with existing production lines.

[0037] Compared to the non-self-healing system (Comparative Example 1), the wear scar diameter of the example was reduced by 53%, and the torque stability was significantly improved; compared to the traditional system (Comparative Example 2), the ultra-low temperature viscosity was reduced by 34%, and the PB value was increased by 25%, solving the industry problems of ultra-low temperature film embrittlement and lack of self-healing of traditional greases.

[0038] In summary, the grease described in this invention, through multi-component synergy and self-repair mechanism, can achieve efficient anti-wear and self-repair at ultra-low temperatures with different parameter combinations, making it suitable for joint lubrication of robots in extreme environments.

[0039] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A low-temperature anti-wear grease for robots, characterized in that, The grease is constructed based on a biomimetic self-healing mechanism and contains the following components by weight percentage: The base oil is 85%-92%, and the base oil is a blend of perfluoropolyether and hydrogenated styrene-isoprene block copolymer in a mass ratio of (70:30)-(85:15). Composite thickener 6%-10%; Microencapsulated repair agent 1%-3%; Auxiliary additives: 0.5%-2%.

2. The robot-specific ultra-low temperature anti-wear grease according to claim 1, characterized in that, The perfluoropolyether has a number-average molecular weight of 2500, a pour point below -80°C, and a kinematic viscosity of 80 mmHg at 40°C. 2 / s.

3. The robot-specific ultra-low temperature anti-wear grease according to claim 1, characterized in that, The hydrogenated styrene-isoprene block copolymer has a styrene content of 28% and a Tg of -65°C.

4. The robot-specific ultra-low temperature anti-wear grease according to claim 1, characterized in that, The composite thickener is composed of lithium 12-hydroxystearate and fluorinated modified montmorillonite in a mass ratio of (4:1) to (6:1).

5. The robot-specific ultra-low temperature anti-wear grease according to claim 4, characterized in that, The fluorinated modified montmorillonite was treated with hexadecyltrimethylammonium bromide intercalation and then surface-modified with a fluorosilane coupling agent.

6. The robot-specific ultra-low temperature anti-wear grease according to claim 1, characterized in that, The microencapsulated repair agent is a core-shell structured microsphere, with the core being a 1:1 molar mixture of dicyclopentadiene and triethylaluminum, and the shell being a hybrid cross-linked network of urea-formaldehyde resin and nano-silica.

7. The robot-specific ultra-low temperature anti-wear grease according to claim 1, characterized in that, The microencapsulated repair agent has a particle size distribution standard deviation of less than 2 μm. After its rupture, the repair agent released on the metal surface forms a polydicyclopentadiene repair film with a thickness of 200-500 nm within 30 seconds, a hardness of 0.8-1.2 GPa, and a friction coefficient of less than 0.

08.

8. The robot-specific ultra-low temperature anti-wear grease according to claim 1, characterized in that, The auxiliary additives include 0.3% of 2,6-di-tert-butyl-p-cresol, 0.1% of N,N′-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine, and 0.6% of fumed silica.

9. The robot-specific ultra-low temperature anti-wear grease according to claim 1, characterized in that, The shell of the microencapsulated repair agent is doped with Fe3O4 magnetic nanoparticles with a particle size of 8-12 nm and a doping concentration of 0.5% of the shell mass.

10. The robot-specific ultra-low temperature anti-wear grease according to claim 1, characterized in that, The microencapsulated repair agent adopts a double-shell structure, with an inner shell of polyurea and a thickness of 0.2 μm, and an outer shell of fluorinated polyacrylate and a thickness of 0.15 μm, with a surface energy of 18 mN / m.